2018
DOI: 10.1007/s10649-018-9823-6
|View full text |Cite
|
Sign up to set email alerts
|

The development of informal statistical inference content knowledge of pre-service primary school teachers during a teacher college intervention

Abstract: Teachers who engage primary school students in informal statistical inference (ISI) must themselves have good content knowledge of ISI (ISI-CK). However, little is known about how college education for pre-service teachers can contribute to the development of their ISI-CK. To address this shortcoming, we used a case study to investigate ISI-CK development in a class of 21 pre-service primary school teachers who participated in a short intervention (180 min). Based on qualitative and quantitative analyses of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
1
2
0
1
Order By: Relevance
“…We found that the pre-service teachers preferred distributed sampling to random sampling, which is consistent with our previous findings (De Vetten et al 2018b) where we argued that this preference for distributed sampling could be due to a sense of loss of control when using random sampling. We called for more research to investigate this sense of control in choosing a sampling method.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that the pre-service teachers preferred distributed sampling to random sampling, which is consistent with our previous findings (De Vetten et al 2018b) where we argued that this preference for distributed sampling could be due to a sense of loss of control when using random sampling. We called for more research to investigate this sense of control in choosing a sampling method.…”
Section: Discussionsupporting
confidence: 91%
“…Most respondents did not seem to understand that a representative sample can be used to draw useful, albeit uncertain, conclusions about an unknown population. So, apart from the unfamiliarity of pre-service teachers with ISI, it could be that many of them are reluctant to make generalizations beyond the data collected because they do not understand this underlying logic of sampling (Watson 2004). In De Vetten et al (2018b, we describe a first attempt at fostering preservice teachers' understanding of this logic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, children show sensitivity to the notion of fairness and inclusion in the sampling process, often in statistically non-normative ways (Meletiou-Mavrotheris & Paparistodemou, 2015). A later study by de Vetten et al (2018) suggests that adults also show similar types of distrust of simple random sampling.…”
Section: Conceptions About Probability and Randomnessmentioning
confidence: 99%
“…E, mesmo não havendo a obrigatoriedade de abordagem de conceitos relacionados a essas medidas, o professor precisa entendê-las, para que compreenda como os números delas resultantes representam as informações quantitativas.A sugestão para a noção de variação dos dados não traz um aprofundamento complexo, mas entende-se como necessária. Nesse sentido, é realmente uma noção, com o entendimento mais conceitual, como por exemplo: a) a variação se refere a quanto os valores podem diferir entre si e pode ser calculada/medida; b) quanto mais próximos um valor do outro menor é o índice de variação, quanto mais dispersos os valores maior é a variação; c) o desvio-padrão é uma medida de variação particularmente importante, pois determina a variação dos dados em relação à média; e d) a interpretação dos desviospadrão deve ser realizada de maneira correta (TRIOLA, 2014) Vetten et al (2018). afirmam a validade do trabalho com a IEI com alunos do ensino elementar e como, essa abordagem, pode ser um importante caminho para o desenvolvimento da habilidade (EF05MA24) da BNCC(2017), que trata da interpretação de dados relacionados a diferentes contextos cotidianos (saúde, trânsito etc.)…”
unclassified